A Comprehensive Approach to Protocols and Security in Internet of Things Technology - Jean Pierre Ntayagabiri; Youssef Bentaleb; Jeremie Ndikumagenge; Hind EL Makhtoum (Universitas Dian Nuswantoro, 2025)
The exponential growth of the Internet of Things (IoT) introduces a multitude of security challenges, as a vast number of connected devices often operate with inadequate protection measures. This vulnerability heightens the risk of cyberattacks, data breaches, and hacking, exposing systems and sensitive information to increased threats. Ensuring security in the IoT ecosystem while considering this rapidly expanding technology's physical limitations and specific requirements is a complex task. This article comprehensively analyzes the primary vulnerabilities and risks associated with IoT, exploring innovative strategies and effective solutions to strengthen its security framework. The article highlights the critical role of secure device authentication, data encryption, regular updates, and continuous monitoring by addressing the intricacies of communication protocols and emphasizing the need for standardization. Ultimately, this work advocates for a holistic approach to IoT security, where robust, adaptable solutions are developed to safeguard against the evolving landscape of cyber threats.